Young children associate buying with feeling richer - Kappes, Heather Barry (Frontiers in Behavioral Economics, 2024)
From an early age, children begin to make decisions about buying things they want, or refraining from buying (e.g., to save up for something better). However, it was unclear how these decisions affect their feelings about their economic resources: does buying make children feel richer or poorer? This manuscript describes three studies that address this gap, with children ages 4 through 12 in the United Kingdom and United States. Older children thought that a child who bought something was richer than a child who refrained from buying, even if the target child was still able to accomplish their goal (Study 1). And for children as young as 4, imagining buying something (compared to imagining refraining from buying) predicted and led to imagining themselves feeling richer (Studies 2–3). The magnitude of the effect of buying vs. refraining on feeling rich did not change appreciably through age 12. These findings complement previous research which looked at children's judgments of their family's social status, by showing that children's feelings about their economic resources also fluctuate in response to actions (buying vs. refraining) that impact those resources. This work contributes to an understanding of how feelings of wealth emerge in childhood and has useful implications for adults who want to support children in developing financial skills.